Prevalence and clinical significance of liver function abnormalities in patients with acute heart failure - Klaudia Vyskocilova (Biomedical Papers, 2015)
Aims: Liver pathology caused by cardiac dysfunction is relatively well recognized, however, its clinical importance has not been fully evaluated. The aim of this study was to assess the prevalence of liver function tests (LFTs) abnormalities and to identify associated factors mediating hepatic impairment in patients with acute heart failure (AHF). Methods: The AHEAD (Acute Heart Failure Database) registry is a database conducted in 9 university hospitals and 5 regional health care facilities in the Czech Republic. From December 2004 to October 2012, the data of 8818 patients were included. The inclusion criteria for the database followed the European guidelines for AHF. Serum activities of all LFTs and total bilirubin were available in 1473 patients at the baseline. Results: In patients with AHF, abnormal LFTs were seen in 76% patients (total bilirubin in 34%, γ-glutamyltransferase in 44%, alkaline phosphatase in 20%, aspartate aminotransferase in 42%, alanine aminotransferase in 35%). Patients with cardiogenic shock were more likely to have LFTs abnormalities compared to mild AHF and pulmonary oedema. LFTs abnormalities were strongly associated with AHF severity (left ventricular ejection fraction and NYHA functional class) and clinical manifestation. While hepatocellular LFTs pattern predominated in left sided forward AHF, cholestatic profile occurred mainly in bilateral and right sided AHF. Additionally, patients with moderate to severe tricuspid regurgitation had significantly higher prevalence of abnormalities in cholestatic LFTs. Conclusions: Defining the LFTs profile typical for AHF plays an important role in management of AHF patients, since it may avoid redundant hepatic investigations and diagnostic misinterpretations.